Taxation and household behavior: Analyzing the impact of tax policies on savings and spending decisions - Mandala, Gangu Naidu; Kusum, Kusum; Appasaba, L.V; Mishra, Jitendra Mohan (The International tax journal, 2025)
Taxation is important as it gives the government income and also effects how individuals make their financial decisions. This study, “Taxation and Household Behavior: Analyzing the Effect of Taxes on Savings and Spending Habits”, looks at the ways that tax rules in India, especially Andhra Pradesh, influence individual decisions about saving and spending. Through studying responses from 180 participants, the research determines that taxes have major effects on how people decide what to do financially by means of incentives, price changes and other influences. According to the findings, knowing about taxes encourages more people to save and using instruments like PPF and ELSS is seen as very helpful. Both mental accounting and framing effects explain other reasons why taxpayers might not always behave rationally. Based on the study, when tax policies are developed using behavioral and fairness considerations, they help families save money, build future plans and withstand economic ups and downs. The study helps fill missing data on taxation and its effect on behavior in Indian households, offering policy proposals that support inclusive financial growth.